Some Thermodynmic Properties of binary Mixtures of Alcohol isomers and Sulfolane at 298.15K (Journal of the College of Basic Education, 2022)
The refractive indices, nD densities , and viscosities h of binary mixtures of sulfolane + n -butanol + sec- butanol + iso- butanol + tert – butanol + n-propanol and iso- propanol were measured at 298.15K. Form experimental data, excess molar volum VE , excess molar refractivity nD, excess molar viscosityhE and excess molar Gibbs free energy of activation of viscous flow DG*E were calculated. From n-propanol – sulfolane and iso- propanol sulfolane mixtures showed negative nD, n-butanol – sulfolane, sec-butanal – sulfolane, iso-butanol – sulfolane and tert- butanol sulfolane , DnD was positive over the whole mole fraction rang , while VE, hE and DG*E show a negative deviation. The results obtained for binary mixtures suggest two types of molecular interaction. One is the formation of new stable complexes between the sulfone group of sulfolane and the hydroxyl group of alcohols and the second is related to the participation in destroying the mixture structure and forming a new structure. Excess molar quantities of these binary mixtures were found to be affected directly by the position of hydroxyl group and the steric associated with the methyl group.